Présence des études sur l’Alsace dans la revue Recherches germaniques - Maryse Staiber (Recherches Germaniques)
To mark the fiftieth anniversary of the journal, this contribution takes a retrospective overview of the publications on Alsace that appeared between 1971 and 2020. While this field of research has been a privileged theme from the very beginning, its presence has varied over the years, revealing both continuity and paradigm shifts. A full synopsis of the summary is included in the paper.